IMPLEMENTASI LIFE SKILLPADA PEMBELAJARAN KIMIA BAHANADITIF - Nurlina Aznam (LPMPP Universitas Negeri Yogyakarta, 2002)
According to Human Development Index (HOI), in the matterofquality in education Indonesia is ranked the l02nd amongthe 106 countries surveyed. Even now dissatisfaction is still feltat all educational levels. Universities are still incaRable of producinggraduates r ady for' th job market and the l'obal competition.Students are not quite dble to link or relate one academicsubject to another and even less able to apply in real life what'they learn from the subjects. Therefore, they should be equippedwith subjects based on life skills.Additive Substance Chemistry is one of the subjects taughtin the Chemistry Course Program of the Department ofChemistry Education, Faculty of Mathematics and PhysicalSciences,State University of Yogyakarta. Its materials arebased on society's actual.needsand presented in. the formof topics and sub-topics of aterials providing . knowledge ofadditive. substance chemistry ..and. class assignments enablingstudents to ap,ply it on various life skills. The teaching, processshould be motivating so that creative ideas will come fromstudents.